The Relationship Between Emotion-Focused Coping, Learning Motivation, and Social Skills and University Students’ Academic Stress - Pradana, Nicko; Muarifah, Alif; Prabawanti, Ciptasari (Psikopedagogia, 2022)
This correlational study aimed to present empirical evidence on the role of emotion-focused coping, learning motivation, and social skills in academic stress.   Respondents were 6th-semester students of the guidance and counseling department at Universitas Ahmad Dahlan Yogyakarta (n=237). The multiple linear regression analysis results showed that emotion-focused coping, learning motivation, and social skills simultaneously affect academic stress. The result of this study provides university counselors with a reference on guidance and counseling services related to emotion-focused coping, learning motivation, social skills, and academic stress.